Donne's Augustine renaissance of cultures of interpretation. - Ettenhuber, Katrin (Oxford Oxford university, 2011)
A comprehensive re-examination of John Donne, through his response to the most iconic religious figure in Western theology, Saint Augustine of Hippo. This book significantly enriches our understanding of the reading and writing culture of Renaissance England, and of the religious debates and controversies in the decades leading up to the Civil War.
Keywords: Augustine, -- Saint, Bishop of Hippo -- Influence; Augustine, -- Saint, Bishop of Hippo -- In literature; Donne, John, -- 1572-1631 -- Criticism and interpretation; Donne, John, -- 1572-1631 -- Religion; Theology -- History -- 17th century